RANCANG BANGUN PENGELOLAAN DATA PELANGGAN BERBASIS WEB DENGAN METODE WATERFALL (Studi Kasus: Penjahit Ibu Kus Sri Midawati) - Muhammad Ruhul Jihad; Sri Mulyati (Journal of Research and Publication Innovation, 2023)
This study aims to produce an application that can store important data needed by tailors using the Waterfall method. This application will facilitate tailoring in the customer data management process. These important data include customer identity, customer body size, customer demand model, type of fabric the customer wants, order taking schedules and others. This system is web-based so that it can be accessed by tailors and customers anytime and anywhere. This system was developed using the PHP programming language and uses MySql as its database, this system uses Black Box Testing as its testing method.